2014
DOI: 10.1021/je5003779
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Phase Equilibrium and Heat Capacity of Binary Mixture 1-Ethyl-3-methylimidazolium Bis(trifluoromethylsulfonyl)imide + 1-Propanol

Abstract: The measurements of the liquid−liquid coexistence curve and the heat capacity for binary mixture {1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C 2 mim][NTf 2 ]) + 1-propanol} have been precisely performed. The values of the critical exponents α and β in the critical region were obtained and coincided well with the 3D-Ising ones. The complete scaling theory was applied to well represent the asymmetric behavior of the diameter of the coexistence curve, indicating an important role of the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…This is the same as for other imidazolium-based IL systems at their UCST mole fraction, i.e. , [C 8 mim][TFSI]–1,4-DIO, 1 [C 2 mim][TFSI]−1-propanol 85 and [C 2 mim][TFSI]−1-butanol, 41 and [C 6 mim][TFSI]−bromobenzene. 86 By contrast, the [C 6 mim][TFSI]–FA- d 2 solution at the mole fractions far from the UCST x FA- d 2 separates upon cooling via the mean-field mechanism.…”
Section: Resultsmentioning
confidence: 71%
“…This is the same as for other imidazolium-based IL systems at their UCST mole fraction, i.e. , [C 8 mim][TFSI]–1,4-DIO, 1 [C 2 mim][TFSI]−1-propanol 85 and [C 2 mim][TFSI]−1-butanol, 41 and [C 6 mim][TFSI]−bromobenzene. 86 By contrast, the [C 6 mim][TFSI]–FA- d 2 solution at the mole fractions far from the UCST x FA- d 2 separates upon cooling via the mean-field mechanism.…”
Section: Resultsmentioning
confidence: 71%
“…The lines are a guide to the eye. [44], () [45], () [46], () [47], () [48], () [49], () [50], () [51], () [52], () [53], () [54], () [55], () [56], () [57], () [58], () [59], () [60], () [61], () [62], () [63], () [64], () [65], () [66], () [67], () [68], () [69], () [70], () [71], () [72], () [73], () [74], () [75], () [76], () [77], () [78], () [79], () [80], () [81], () [82], () [83], () [84], () [85], () [86], () [87], () [88], () [89], () [90], () [91], () [92]...…”
Section: Methodsunclassified
“…19 Table 5 lists the critical reduced temperatures and the critical reduced densities for the binary ionic liquid solutions determined in this study and reported previously. [21][22][23][24]26,27,32,33,[39][40][41][42][43] The Monte Carlo simulation predicted the RPM values of the ionic solutions to be 0.08 and 0.05 for r c * and T c *, respectively, regardless of e r,c and s. 11 However, the experiments exhibited that the values of T c * and r c * of the ionic solutions generally increased with the e r,c of their solvents. This is attributed to the fact that the solvophobic interactions become important and visible as the coulometric force was screened.…”
Section: The Dependences Of the Critical Reduced Parameters On The Re...mentioning
confidence: 99%